Dietary strategies for the prevention of obesity. - Jebb, SA (2005)
The rising tide of obesity has led to a resurgence of interest in dietary strategies to prevent excess weight gain. Data from controlled intervention studies is sparse, but nonetheless evidence from other diverse sources has identified a number of specific dietary factors and aspects of eating behaviour that either promote or protect against obesity. The present paper reviews the evidence in relation to energy density, the macronutrient composition of the diet, including the nature of carbohydrate foods and sugar-rich drinks, portion size and snacking habits. It concludes that there is now sufficient evidence to develop clear dietary guidelines to prevent weight gain that are largely consistent with those for the prevention of CVD and cancer. However, coordinated action across multiple stakeholders is also required if these guidelines are to be translated into sustained changes in eating habits.